1999
DOI: 10.1177/1358836x9900400108
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation and triggering of cardiovascular events

Abstract: Myocardial infarction and sudden cardiac death demonstrate a marked circadian variation with an increased risk during the morning after awakening and arising. The recognition of the morning increase of acute cardiovascular events has convinced many that they may be triggered by morning activities. It is of note, however, that cardiovascular events occur throughout the day -even if at lower frequency compared with the morning.There is a strong association between external triggers and the onset of myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
(79 reference statements)
2
12
1
3
Order By: Relevance
“…7 Trigger factors have been estimated to play a causative part in 20% of cases of acute coronary syndrome. 18 Our results do not identify the trigger factors that may have provoked the additional deaths observed. Losing at home may lead to anger, frustration, or depression among supporters, which are known to increase the risk of acute coronary and cerebrovascular events including sudden death.…”
Section: Discussioncontrasting
confidence: 65%
“…7 Trigger factors have been estimated to play a causative part in 20% of cases of acute coronary syndrome. 18 Our results do not identify the trigger factors that may have provoked the additional deaths observed. Losing at home may lead to anger, frustration, or depression among supporters, which are known to increase the risk of acute coronary and cerebrovascular events including sudden death.…”
Section: Discussioncontrasting
confidence: 65%
“…Therefore, if on-duty CHD events had no relation to work, firefighter deaths should have a circadian pattern similar to the general population in whom cardiovascular events peak between 6 am and noon [45-48]. In stark contrast, we found most on-duty CHD fatalities occurred between noon and midnight.…”
Section: Discussionmentioning
confidence: 55%
“…In fact, bad news can be defined as a sudden emotional stress. Between 20 and 40% of sudden cardiac deaths are precipitated by acute emotional stressors [6,11]. Studies in both animal models and humans confirmed a causal relationship between emotional stress and coronary atherosclerosis [12,13].…”
Section: Discussionmentioning
confidence: 99%